The effects of economic growth, interest rate and international trade on Islamic banking financing / Wan Nur Hasyimah Wan Hanafi - Wan Hanafi, Wan Nur Hasyimah (2013)
Many previous studies have focused on the impact of finance on economic growth. However, few studies have examined the impact of economic growth on Islamic banking. Islamic banking industry has received much attention from people around the world today. Therefore, it is important to know whether the macroeconomic variables of economic growth will affect the Islamic banking financing. Based on (2007:1 - 2012:4) quarterly data, the purpose of this study is to investigate the relationships of gross domestic product (GDP), interest rate and trade activities toward the Islamic banking financing in Malaysia. The study has been done using time series analysis available in STATA software. This paper also employs the cointegration test and Vector Error Correction Model (VECM) to see whether Islamic banking development has short-run and long-run run relationship with all the economic variables. The results illustrated there is no relationship between the variables in the short-run. However, in the long-run, the results show that Islamic banking financing has a positive relationship with trade, while it shows a negative relationship towards GDP and interest rate. For future studies, a wider scope is recommended where more determinant factors can be taken into account.